Drying kinetics and thermodynamic properties of ‘baru’ almond flours - Alves,Niedja M. C. (2021)
ABSTRACT The consumption of flour and oil of ‘baru’ (Dipteryx alata Vogel) has increased due to its nutritional characteristics; however, there are few studies on the processing of the flour of this almond. The aim of this research was to study the drying kinetics of the whole and partially defatted flours of ‘baru’ almond, the residue of the oil extraction, as well as its thermodynamic properties. The whole flour was obtained by the grinding of seeds and the partially defatted flour by chemical extraction. The products were dried with forced air circulation oven at 60, 70 and 80 °C. Ten models, commonly used for drying, were selected for fitting. Based on statistical criteria, the Midilli model was selected to represent the drying kinetics of ‘baru’ almond flour. The difference in the drying rate between the flours tended to attenuate with the elevation of the temperature. Activation energy was 39.24 kJ mol-1 for the whole flour and 29.01 kJ mol-1 for partially defatted flour. Enthalpy and entropy decreased with increasing temperature, whereas Gibbs free energy increased. For the flour with highest oil concentration, the thermodynamic properties were higher than for the one with lowest oil concentration.